Real-Time IoT-Enabled Multi-Modal Warning System for Preventing Vehicular Brake Fade Accidents - Yulio, Brian Adam Dwi; Marwanto, Riza Phahlevi; Shofiah, Siti; Humami, Faris; Muthoriq, Ery; Wibowo, Helmi (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2026)
Brake fade due to excessive heat remains a leading cause of vehicular accidents, particularly among heavy-duty and public transportation vehicles. This issue is exacerbated by the limitations of conventional brake monitoring systems that lack real-time response capabilities. To address this challenge, this study develops a Smart Brake Thermal Management system based on Internet of Things (IoT) technology, designed to detect and deliver multi-modal alerts in response to potential brake overheating. The system integrates precision thermocouple sensors, an ESP32 microcontroller, an OLED display, and cloud-based notifications via Telegram. Using a Research and Development (R&D) methodology, the system was validated through six controlled road tests under standardized conditions. Results indicate high temperature measurement accuracy at 98.07% and 98.62% for dual sensor configurations, with system response times of less than two seconds. The warning mechanism effectively delivered synchronized notifications via visual indicators, audible alerts, and instant messaging. This system demonstrated a strong ability to identify the risk of brake fade before critical failure occurred, enhancing vehicular safety significantly. Its modular design and cost-effective implementation also make it suitable for large-scale retrofitting in existing vehicle fleets. The primary contributions of this research include the integration of multi-modal warning systems, real-time thermal monitoring through cloud connectivity, and a predictive approach to brake temperature management that improves proactive safety interventions.